Characterization of plasmid-borne afa-3 gene clusters encoding afimbrial adhesins expressed by Escherichia coli strains associated with intestinal or urinary tract infections. - Le Bouguenec, C (1993)
The afa gene clusters encode afimbrial adhesins (AFA) that are expressed by uropathogenic and diarrhea-associated Escherichia coli strains and belong to a family of hemagglutinins recognizing the Dr blood group antigen as a receptor. This family so far includes AFA-I and AFA-III as well as the Dr and F1845 adhesins (B. Nowicki, A. Labigne, S. Moseley, R. Hull, S. Hull, and J. Moulds, Infect. Immun. 58:279-281, 1990). Reported in this work is the genetic organization of the afa-3 gene cluster cloned from a uropathogenic E. coli strain (A30) which expressed a subtype of AFA designated AFA-III. The amino acid sequence of AFA-III was deduced from the nucleotide sequence of the afaE3 gene and was found to be highly homologous to that of the Dr adhesin (98.1% identity). A polymerase chain reaction assay was developed to detect the presence of afa-3 gene clusters in E. coli strains. Study of the genetic support of the afa-3 gene clusters in the strains which showed positive amplification revealed that they were always located on large, 100-kb plasmids whether the strains originated from patients with cystitis or with diarrhea. Moreover, the cloned afa-3 gene clusters from A30 and from the diarrhea-associated strain AL845 appeared to be carried by 9-kb plasmid regions which displayed a similar genetic organization. Chloramphenicol was reported to be a potent inhibitor of receptor binding by the Dr adhesin (Nowicki et al., Infect. Immun. 58:279-281, 1990). AFA-III expressed by strains AL845 and AL847 appeared to mediate, like the Dr adhesin, chloramphenicol-sensitive hemagglutination, whereas AFA-III produced by A30 conferred chloramphenicol-resistant adherence. A comparison of the sequences of these four proteins indicated that the amino acid at position 52 of the processed AFA could be part of the receptor-binding domain.